Trading System Analysis and Marketing Margins for Tuna, Cakalang, and Tongkol at Fish Auction Place (TPI) Kuala Idi, East Aceh District - Pratama, Agus; Haser, Teuku Fadlon; Rizky, Devi Yanti; Novita, Dina; Dahara, Julia; Fadli, Fadli; Febri, Suri Purnama; Darsiani, Darsiani (Jurnal Ilmiah Samudra Akuatika, 2022)
Marketing of fishery products must be carried out efficiently so that fishermen and consumers are not harmed. The purpose of this study was to analyze the marketing system, margin value, fisherman's share for skipjack, tuna and tuna in TPI Kuala Idi. Determination of respondents using purposive sampling method. The results of the study were obtained for Cakalang fish, the total marketing margin on marketing channel II was greater, namely Rp. 5,800 and channel I obtained the highest Df, namely 89%. For Tuna, the total marketing margin in marketing channel II is greater, namely Rp. 6,400 and channel I obtains the highest Df, namely 86%. For tuna, the total marketing margin on marketing channel II was greater, namely IDR 5,800 and channel I obtained the highest Df, namely 87%. From the results of Fisherman's Share calculations, the three marketing channels above the percentage share received by fishermen from TPI is 89% and is the largest percentage of other marketing calculations. It can be concluded that the marketing agency TPI Kuala Idi, East Aceh District plays an important role in the share of the results received by fishermen.